Body and Spirit in the Middle Ages : Literature, Philosophy, Medicine - Gubbini, Gaia (2020)
A crucial question throughout the Middle Ages, the relationship between body and spirit cannot be understood without an interdisciplinary approach - combining literature, philosophy and medicine. Gathering contributions by leading international scholars from these disciplines, the collected volume explores themes such as lovesickness, the five senses, the role of memory and passions, in order to shed new light on the complex nature of the medieval Self.